Closure state measurement of final joint of the immersed tunnel of the Hong Kong-Zhuhai-Macao Bridge - SUO Xuhong; LIU Guohui; ZHANG Dejin; GUAN Minglei (Shenzhen Daxue xuebao. Ligong ban)
The immersed tunnel of the Hong Kong-Zhuhai-Macao Bridge adopts the construction mode of sinking from the east and west artificial islands to the middle to form a closed dragon mouth, and then sinking the final joint through. The final joint state parameter measurement is the key factor determining the success or failure of the project. Aiming at the problems of low efficiency, low measurement accuracy, poor reliability and inability to adjust the state of the closure in real time, this paper proposes a real-time measurement method for the formation of the closure state. Firstly, the measurement feature points are arranged on the end faces of the two pipe joints that form the closure, and the coordinates of the feature points in the pipe joint coordinate system are obtained by measurement. Secondly, in the process of sinking and laying, the measuring tower method and the manhole casting point method are used to measure and adjust the state of the closing mouth. Finally, the three measurement results are uniformly converted into the engineering coordinate system, and the accuracy is compared and analyzed by using the measurement error transfer model, and the best measurement method for the closing state of the immersed tunnel construction is obtained. This method changes the construction method of forming closure first, then measuring through and then adjusting accurately in the construction of immersed tunnels, and provides a reference for large-scale underwater installation projects such as immersed tube tunnels and underwater pipes.